Physiological responses to hypothermal stress of Tra catfish (Pangasianodon hypophthalmus) subjected to different feeding rates - Yen-Chun Lee; Yu-Ting Huang; Chin-Chyuan Chang; Yu-Hung Lin (Aquaculture Reports, 2023)
One of the most vulnerable impacts of climate on aquaculture is abnormally low temperature. The present study aimed to evaluate the effects of different feeding rates on physiological responses of Tra catfish (Pangasianodon hypophthalmus) exposed to hypothermal stress. The experimental diets were fed to triplicate groups of fish (initial weight of 6.77 g) with four feeding rates (2%, 3%, 4% and 6% of wet body weight) in a recirculation system for 4 weeks. After the feeding trial, rearing water temperature was lowered from 30 ℃ to 23 ℃ and maintained at 23 ℃ for 24 h. Fish fed 6% diet exhibited higher (p < 0.05) body weight gain, specific growth rate, and condition factor than other treatments. Before hypothermal exposure, plasma glucose and triglyceride concentrations exhibited a linearly increase as the feeding rate increased. The levels of hepatic HSP70 and HSP90 levels decreased with increasing the feeding rates for the fish. At 24 h hypothermal exposure, plasma glucose, triglyceride, and lactate of the fish increased by increasing the feeding rates. Fish subjected to 3%–6% feeding rates reduced hepatic HSP70 level after exposure to hypothermal stress; fish subjected to 2% feeding rate reduced hepatic HSP90 level after exposure to hypothermal stress. The results indicate that the optimal feeding rate for Tra catfish, sized from 6.7 g to 24.7 g, is recommended to be 6% to improve growth performance and physiological responses under hypothermal stress. Furthermore, the hepatic HSP90 but not HSP70 is the main protection protein in Tra catfish exposed to hypothermal stress.